2022
DOI: 10.1136/bmjgh-2021-007878
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related healthcare impacts: an uncontrolled, segmented time-series analysis of tuberculosis diagnosis services in Mozambique, 2017–2020

Abstract: IntroductionCurrently, COVID-19 dominates the public health agenda and poses a permanent threat, leading to health systems’ exhaustion and unprecedented service disruption. Primary healthcare services, including tuberculosis services, are at increased risk of facing severe disruptions, particularly in low-income and middle-income countries. Indeed, corroborating model-based forecasts, there is increasing evidence of the COVID-19 pandemic’s negative impact on tuberculosis case detection.MethodsApplying a segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
5
17
0
Order By: Relevance
“…The impact on national-level TB notifications in 2020 (14.4%) was similar to that reported in Mozambique (15.1%) 3 , but lower than in India, that had a relative loss of cases of 63.3% during the period from March 2020 through April 2021. 16 Other studies estimated the effect of the pandemic on TB case notifications with different approaches and also have found an immediate impact.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The impact on national-level TB notifications in 2020 (14.4%) was similar to that reported in Mozambique (15.1%) 3 , but lower than in India, that had a relative loss of cases of 63.3% during the period from March 2020 through April 2021. 16 Other studies estimated the effect of the pandemic on TB case notifications with different approaches and also have found an immediate impact.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the majority of the prison population in Brazil are young men, and although the number of TB cases in this population had been increasing in the country, a Brazilian TB Bulletin launched in the TB World Day in 2022 reported a decrease of TB case notification in prison population during the pandemic years 26 , suggesting that TB case finding in this population may also have suffered the impacts of the pandemic.Similar to ours findings, in the first year of the pandemic a study in Mozambique found that men were the most affected in terms of TB notification, resulting in a 15% (95% CI 4.0 to 25.0) relative loss, and suggested that this was due to the privileges that women and children had in the country to access health services 3. On the other hand, a study in Zambia found that the proportional distribution of TB notifications according to sex did not significantly differ over the pandemic period 27.…”
supporting
confidence: 88%
See 3 more Smart Citations